MBA Theory and Application of Business and Management Principles - Machado, Carolina; Davim, J. Paulo (Management and Industrial Engineering, 2016)
This book focuses on the relevant subjects in the curriculum of an MBA program. Covering many different fields within business, this book is ideal for readers who want to prepare for a Master of Business Administration degree. It provides discussions and exchanges of information on principles, strategies, models, techniques, methodologies and applications in the business area.